2021
DOI: 10.21203/rs.3.rs-727941/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Humoral and cellular responses after a third dose of BNT162b2 vaccine in patients with lymphoid malignancies

Abstract: BACKGROUND: Immunocompromised patients such as patients with hematological malignancies have impaired immune response to two doses of BNT162b2 (Pfizer / BioNtech) vaccine against SARS-CoV-2. Evaluation of a repeated immune stimulation with a third vaccine dose is needed.METHODS: a vaccine monitoring observatory was conducted in outpatients who were treated for lymphoid malignancies (LM) to monitor both immune and cellular response measured the day of administration of the dose 3 of the mRNA vaccine BNT162b2 an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…25,43 Overall, T-cell immune responses seem generally maintained, although reduced, especially in patients with hematologic malignancies, in comparison to patients with solid tumors and to healthy individuals, both after COVID-19 infection and after a complete vaccination, with predominance of CD4þ responses over CD8þ. 21,25,47,51,58 Systemic therapies did not have a major effect on cellular responses, except for higher suppression rates of CD4þ activity among patients treated with ICIs. 25 In the VOICE clinical trial, almost half of the vaccine non-responders and suboptimal responders to humoral immunity developed a Spike-specific T-cell response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25,43 Overall, T-cell immune responses seem generally maintained, although reduced, especially in patients with hematologic malignancies, in comparison to patients with solid tumors and to healthy individuals, both after COVID-19 infection and after a complete vaccination, with predominance of CD4þ responses over CD8þ. 21,25,47,51,58 Systemic therapies did not have a major effect on cellular responses, except for higher suppression rates of CD4þ activity among patients treated with ICIs. 25 In the VOICE clinical trial, almost half of the vaccine non-responders and suboptimal responders to humoral immunity developed a Spike-specific T-cell response.…”
Section: Discussionmentioning
confidence: 99%
“…OCTAVE DUO trial). 51,68,76,78,[80][81][82][83][84] Furthermore, in the CAPTURE clinical trial, previous SARS-CoV-2 infection boosted vaccine-induced responses, lending further support for a third dose in vulnerable populations. 25 In line with these trends, many countries and institutions have already recommended that severely immunocompromised patients (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the oncology field, three studies with currently available data evaluated the impact of early D3 vaccine injection in poor humoral responders’ patients with LM ( 42 ), with thoracic cancer ( 35 ) and in allogenic transplanted patients in remission of a HM ( 43 ). Nevertheless, these studies employed different serological assays rendering data comparison rather difficult, unless using the conversion factors proposed by the World Health Organization (WHO) (NIBSC code 20/136).…”
Section: Introductionmentioning
confidence: 99%
“…In the first study, Re et al, while using Roche Elecsys assay, demonstrated that LM patients with positive anti-S Abs titers after D2 similarly exhibited increased neutralizing antibodies (Nabs), with a > 80% correlation between Nabs levels and anti-S Abs titers above > 400 BAU/mL ( 42 ). In patients with multiple myeloma, the median anti-S Abs titer prior to D3 was 100 BAU/mL, rising to 2700 BAU/mL (p <0.0001) thereafter, which is comparable to anti-S Abs serum levels from vaccinated healthy donors 6 to 8 weeks after D2 ( 7 ), using the same technique.…”
Section: Introductionmentioning
confidence: 99%